La préfecture du Val-d’Oise édifiée par Henry Bernard à Cergy-Pontoise - Léo Noyer Duplaix; Emmanuelle Philippe (In Situ)
The Department of Val-d’Oise was created by the law of July 10, 1964, which modified the territorial administration of the Paris region. While Pontoise was designated as regional capital, the prefectural services were installed in the middle of the fields, in the neighbouring town of Cergy. The Prefecture building of Val-d’Oise was inaugurated in July 1970. This building was the first major structure within the newly urbanised neighbourhood of Cergy-Prefecture, the centre of the new town of Cergy-Pontoise. The design of this Prefecture, established ex nihilo, was commissioned from the architect Henry Bernard, who took up the challenge of a corbelled construction and imagined a huge inverted pyramid, built on a square base. Embellished by facing sculptures by François Stahly and decorated by Joseph-André Motte, this Prefecture was an attempt at a typological renewal. Described as a ‘welcoming home’, where ‘accessibility for all was the first priority’, the building was an attempt to renew administrative architecture through its interior design, volumes and localisation.